THE EFFECT OF EQUALIZING EDUCATION QUALITY ON STUDENT LEARNING OUTCOMES IN FRONTIER, OUTERMOST, AND LEAST DEVELOPED AREAS (3T) - Widyana, Aminnatul; Puspitasari, Erfina; Kusumawati, Nine Indah; Sutrisno, Zeni (Jurusan Sastra Indonesia, 2023)
The implementation of education in facing various issues or new challenges requires the latest efforts and innovations in handling them. The equalization of educational quality, particularly in frontier, outermost and least developed areas (known as the